2011
DOI: 10.1007/s10869-011-9242-5
|View full text |Cite
|
Sign up to set email alerts
|

Job Design and the Employee Innovation Process: The Mediating Role of Learning Strategies

Abstract: Purpose The purpose of this article is to examine whether employee learning strategies is a mechanism through which job design affects the employee innovation process. In particular, we test whether work-based learning strategies mediate the relationship between job design characteristics (job control and problem demand) and key components of the innovation process (idea generation, idea promotion, and idea implementation). Design/Methodology/Approach Data were collected from a survey of 327 employees in a UK … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(95 citation statements)
references
References 79 publications
2
74
0
8
Order By: Relevance
“…First, the complexity of the relation between job characteristics and employee outcomes is rarely taken fully into account. Although theoretical models like the Job Demands-Resources model of Bakker & Demerouti (2007) stress the need to focus on the interaction effects between various job characteristics, this is rarely put into practice (Holman et al, 2011;Martín, Salanova, & Maria Peiro, 2007). Second, various studies have established the fact that HR practices like reward policies (Baer, Oldham, & Cummings, 2003;Dewett, 2004) have different effects on employees, depending on their personal and group characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…First, the complexity of the relation between job characteristics and employee outcomes is rarely taken fully into account. Although theoretical models like the Job Demands-Resources model of Bakker & Demerouti (2007) stress the need to focus on the interaction effects between various job characteristics, this is rarely put into practice (Holman et al, 2011;Martín, Salanova, & Maria Peiro, 2007). Second, various studies have established the fact that HR practices like reward policies (Baer, Oldham, & Cummings, 2003;Dewett, 2004) have different effects on employees, depending on their personal and group characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The response point of scale consists of five points used (1=Never, 5=Always). The developed scale of Holman et al [26] is used to measure the Cognitive learning strategies. The total items of the scale are 8.…”
Section: Methodsmentioning
confidence: 99%
“…Holman, Totterdell, Axtell, Stride, Port, Svensson & Zibarras, 2012) suggested that SRL has a significant positive effect on the innovative work behaviour of employees. The results of this study complement these works by demonstrating that, at the individual level, SRL is a significant antecedent of IIB.…”
Section: Self-regulated Learningmentioning
confidence: 99%